Effect of tetraethoxy-silane (TEOS) amounts on the corrosion prevention properties of siloxane-PMMA hybrid coatings on galvanized steel substrates - Longhi, Marielen (2015)
Siloxane-poly(methyl methacrylate) (PMMA) organic-inorganic hybrid coatings were deposited on galvanized steel by the dip-coating sol-gel technique. Anticorrosion properties, as well as the morphological, surface and structural features were studied. Hybrid coatings were synthesized from tetraethoxy-silane (TEOS) and methyl methacrylate (MMA) as inorganic and organic phases, respectively, linked by 3-metacriloxypropyl-trimethoxysilane (TMSM) as a coupling agent. The MMA/TMSM ratio was kept constant, whereas the four TEOS/TMSM ratios were varied. The characterization of coatings was assessed using several techniques such as Scanning Electronic Microscopy (SEM), Contact Angle, Fourier Transform Infrared (FT-IR), Open Circuit Polarization (OCP), Atomic Force Microscopy (AFM) and Electrochemical Impedance Spectroscopy measurements (EIS). The EIS results, which were obtained for the hybrid coatings, were discussed based on an electrical equivalent circuit used to adjust the experimental data. The results showed that the increasing the TEOS content caused increase in coating thickness, increased in the surface roughness and increased in the surface hydrophobicity. The film with the highest TEOS content presented the best electrochemical performance, more effective in protecting against corrosion.